The sense of being there during online classes: analysis of usability and presence in web-conferencing systems and virtual reality social platforms. Issue 12 (10th September 2021) - Chessa, Manuela; Solari, Fabio
ABSTRACT: Due to the Covid-19 pandemic, millions of people had to stay at home for several months and to move their everyday activities online. From smart-working to online learning, also considering entertainment activities, people started to extensively use platforms for remote communication and for sharing video, text, and audio content. Such systems are able to cope with the need of communicating, but the common feeling is that people, and especially students, are missing the physical relationships with classmates and colleagues. In this paper, we analyse two modalities that can be used to give an online University lecture, by focusing on the 'sense of presence', i.e. on the ability to produce into students the psychological sense of being in a classroom together with the teacher and their classmates. We consider a standard web-conferencing system, and a Virtual Reality social platform. We also take into account the 'usability' factors, to understand if extended reality systems could be, in a near future, a possible alternative to improve distance lectures and meetings.